Comportamiento agronómico de 50 líneas avanzadas F6 de arroz Oryza sativa L. ssp. japonico y su calidad molinera. - Alvarado Torres, Kevin Alexander (2021)
This research was developed in the CEDEGE Project area, located in the Babahoyo canton, Los Ríos province, with geographic coordinates 01º50´1.85” South Latitude and 79º 26´ 47.26” West Longitude at an altitude of 9 meters above sea level. The main objective was to study the agronomic behavior of 50 advanced F6 lines of rice (Oryza sativa L. ssp. japonico) and their milling quality. The genetic material consisted of a total of fifty F6 segregating lines of Japanese type rice, and three commercial controls, such as cultivars INIAP FL-1480, SFL-011 and INIAP FL-Arenillas. The evaluated variables were the morpho-agronomic and productive characteristics and milling quality; in addition, the experimental design of Complete Random Blocks (DBCA) with three repetitions was used, and the comparison of the means was carried out by means of the Tukey test. The management of the trial began with the sowing of the seedbed, and the work of the crop that includes conventional management was carried out, highlighting the sowing, pre-emergent and post-emergent weed control, fertilization, phytosanitary control and harvest. Regarding the determination of the milling characteristics, the samples were processed in a specialized laboratory of the Santa Rosa milling machine, located in the Santa Lucia canton, Guayas province with geographic coordinates 01º46´12.8 ” South Latitude and 79º 59´ 05.7” Longitude West. Based on the results, it is concluded that the studied lines 3, 14 and 44 appear as very vigorous plants, with characteristics similar to commercial varieties. In addition, most of the lines obtained an average height of less than 130 cm. A large part of the lines have early flowering, most of the lines also obtained an adequate number of tillers per plant, behaving as materials with a high level of tillering; however, all the lines evaluated are equal in the amount of panicles that produce per plant. There were no statistical differences regarding the amount of grains per panicles they produced. Approximately 17 lines have a short grain length between 4.5 and 4.6 mm. A large part of the lines obtained excellent yields. There were no significant differences between the lines in terms of impurities, weight of chaff, brown rice, white mass, and flower grains.